Gauging the link between different views of aging facets and their associations with cognitive and mood functioning in midlife and older age: a cross-sectional study - Carbone, Elena; Paccagnella, Omar; Borella, Erika (Frontiers in Psychology, 2025)
ObjectivesPersonal Views of Aging (VoA) encompass different constructs capturing individuals' perceptions, attitudes, and expectations regarding their aging self, which are well-established influences of health-related and longevity outcomes over the adult life course. The present study aimed to investigate the associations among personal VoA facets, namely subjective age, Attitudes Toward Own Aging (ATOA), and Awareness of Age-Related Change (AARC), and their joint contribution in explaining mood and cognitive functioning in midlife and older age.MethodA sample of 350 community-dwelling individuals aged 40 to 92 years reported their mental felt age and completed the Attitudes Toward Own Aging scale (ATOA) and the Awareness of Age-Related Change questionnaire (AARC), assessing perceptions of age-related gains (AARC-Gains) and losses (AARC-Losses) in various functioning domains. They were also administered a working memory and a mood measure. Structural equation models were used to examine the associations between personal VoA, cognitive and mood outcomes.ResultsResults revealed that AARC is more likely to act as a mediator between the global personal VoA facets and the mood outcome but not the cognitive one. Specifically, more positive ATOA scores were associated with high AARC-Gains and low AARC-Losses, and AARC-Losses were in turn associated with better mood functioning. Moreover, a youthful mental felt age was associated with higher ATOA and AARC-Gains scores, whereas greater AARC-Gains and AARC-Losses were associated with a poorer working memory performance.DiscussionThese findings suggest a complex interplay between facets of personal VoA and further highlight their contributions to explaining particularly mood outcomes in midlife and older age.